De novo deletion (14)(q11.2q13) including PAX9: clinical and molecular findings. Issue 3 (1st March 1999) - Schuffenhauer, Simone; Leifheit, Hans-Jürgen; Lichtner, Peter; Peters, Heiko; Murken, Jan; Emmerich, P
Abstract : A 3 year old boy with a de novo deletion (14)(q11.2q13) of paternal origin encompassing the region from D14S264 to D14S70 is described. The patient presented with severe psychomotor retardation, bilateral cleft lip/palate, bilateral colobomas of the optic nerves and retinas, agenesis of the corpus callosum, pes calcaneovarus, reduced oesophageal peristalsis, and swallowing difficulties. This is the first reported case of PAX9 hemizygosity in humans. Haploinsufficiency of the PAX9 gene might be expected to cause some of the developmental defects and the dysphagia. Another haploinsufficiency candidate gene, the bZIP transcription factor gene NRL, which is specifically expressed in neuronal cells and the eye during embryogenesis, was excluded from the deletion interval.